Comparison of the efficacy and safety of 308‐nm excimer laser with intralesional corticosteroids for the treatment of alopecia areata: A randomized controlled study. Issue 4 (2nd December 2021) - Kianfar, Nika; Dasdar, Shayan; Mahmoudi, Hamidreza; Abedini, Robabe; Fahim, Shabnam; Hosseini, Seyed Amirhossein; Daneshpazhooh, Maryam
Abstract: Background: Corticosteroids have been the mainstay of treatment for alopecia areata (AA). Recently, the 308‐nm excimer laser has been proposed for treating AA. Objectives: To compare the efficacy and safety of excimer laser with intralesional corticosteroid (ILCS) in AA. Methods: Patients with at least two alopecic patches were randomly assigned to receive weekly excimer laser treatments or monthly injections of ILCS. Photographs and trichoscopy images were examined at baseline, the last treatment session, and after one month of follow‐up. The hair regrowth score was evaluated on a 6‐point scale. Results: Sixteen patients with 99 alopecic patches completed the study. At the last treatment session, the mean score of hair regrowth for the laser was significantly lower than the ILCS ( p  = 0.003). However, after a month of follow‐up, the difference was not statistically significant ( p  = 0.148). Positive response in hair regrowth (≥50%) was achieved in 47% of laser‐treated patches and 66% in ILCS‐treated ones. Four (25%) and 8 (50%) patients experienced severe adverse events of laser and ILCS, respectively. Conclusions: The excimer laser was safe and effective in AA. The effect of laser on hair regrowth might be delayed as compared with ILCS.